2017
DOI: 10.1158/1055-9965.epi-17-0170
|View full text |Cite
|
Sign up to set email alerts
|

Preanalytical Stability of Antibodies to Pathogenic Antigens

Abstract: Serologic testing for antibodies against epitopes from pathogens is a valuable tool for investigating the relationship between infection and disease. This study comprehensively evaluates the impact of preanalytic variation on antibody seropositivities to a selected set of antigens arising from delays in processing of blood samples, preprocessing storage temperature, and vacutainer type. We assessed peripheral blood collected from 29 volunteers in four different Vacutainer types [ethylenediaminoetetraacetic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…However, as shown here, antibodies tend to be stable analytes; the mean elapsed time between Tasso sample collection and processing was 72.7 hours, a relatively long period of time. Hodgkinson and colleagues also evaluated the effect of delayed processing and temperature on results from a multiplex immunoassay measuring antibodies against various infectious antigens and found their results to be stable at room temperature through 6 days [ 6 ]. Their results are consistent with our clinical experience evaluating the time-dependent stability of samples tested by antibody binding assays.…”
Section: Discussionmentioning
confidence: 99%
“…However, as shown here, antibodies tend to be stable analytes; the mean elapsed time between Tasso sample collection and processing was 72.7 hours, a relatively long period of time. Hodgkinson and colleagues also evaluated the effect of delayed processing and temperature on results from a multiplex immunoassay measuring antibodies against various infectious antigens and found their results to be stable at room temperature through 6 days [ 6 ]. Their results are consistent with our clinical experience evaluating the time-dependent stability of samples tested by antibody binding assays.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that antibody concentrations in the serum are stable at 4 °C for short times ( Hodgkinson et al, 2017 ; Rodriguez-Capote et al, 2016 ). Our study results agree with those of previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that confounding methodological factors should be ruled out ( Chaigneau et al, 2007 ; Hodgkinson et al, 2017 ). To the best of our knowledge, no study has systematically described the methodology of sample preparation and storage with respect to important antibodies as blood biomarkers of kidney disease.…”
Section: Introductionmentioning
confidence: 99%
“…Serum, which, unlike plasma, lacks fibrinogen and clotting factors, is traditionally used for antibody reactivity and functional assays. While prior studies by us and others show that the anticoagulants heparin and EDTA in plasma have little effect on antibody reactivities to M. tuberculosis and other mycobacterial antigens, little is known about the effects of ACD and CPT plasma on antibody reactivities, especially in the context of TB [7][8][9]. Furthermore, we and others previously showed that antibodies to M. tuberculosis antigens can have Fcgamma receptor (FcyR)-mediated functions, such as the uptake of M. tuberculosis into macrophages [1][2][3].…”
Section: Introductionmentioning
confidence: 98%